The role of corporate entrepreneurship in internationalization of Small and Medium Manufacturing Enterprises (SMEs) - Chelliah, Shankar; Sulaiman, Mohamed; Munusamy, Jayaraman (Common Ground, 2010)
Many researchers and practitioners from the industry would agree on the importance of corporate entrepreneurship as an effective means for rejuvenating companies and improving their financial performance. In the era of intense global competition, Small and Medium Enterprises (SMEs) realize that a greater focus is required in entrepreneurial behaviors in identifying foreign market opportunities, seeking partnerships with foreign firms, and building organizational capabilities in order to enhance their competitive advantage. But, what do we really know about the role of corporate entrepreneurship on internationalization among the SMEs? Most of the studies focus on corporate entrepreneurship among established companies who have strengths in both resources and reputations in the market. Within this context, this article describes a study of corporate entrepreneurship and its role in SMEs internationalization. Data were collected from 300 internationalized SMEs in Malaysia, from manufacturing industry representing consumer and industrial products. Regression analysis was then used to analyze the data. The study also examines the impact of size as a moderating variable between corporate entrepreneurship and internationalization. The results suggest that corporate entrepreneurship has a positive impact on internationalization when size functions as moderating factor in relatively smaller firms. This effect on the internationalization, indicates that corporate entrepreneurship is particularly effective practice among SMEs when the companies are small. This study poses two implications for practicing managers and policy makers. First, the study encourages SMEs to nurture corporate entrepreneurship from the beginning or at inception as it pave path for firm internationalization. Second, the study suggests a need to use a long term horizon to judge entrepreneurial actions and its impacts on the firm internationalization.